The Effectiveness of Basil Leaves Extract (Ocimum basilicum L.) on Histopathological Features of The Lung Rattus Norvegicus Exposure to Mosquito Coil Smoke - Pitaloka Kurniasari; Iwan Sahrial Hamid; Mirza Atikah Madarina Hisyam (Journal of Applied Veterinary Science And Technology, 2025)
Background: Mosquito coil smoke is one of the exogenous free radicals. Exposure to mosquito coil smoke is associated with lung inflammation, oxidative stress and lipid peroxidation. Compounds that can inhibit the oxidation reaction by binding free radicals are known as antioxidants. Purpose:  This study aims to determine the effectiveness of basil leaf extract (Ocimum basilicum L.) as an antioxidant on damage to the histological structure of the lung of white rats (Rattus norvegicus) exposed to mosquito coil smoke. Method: Rats were divided into five groups;  group without treatment as negative control C(-) was given 0.5% CMC Na, group as positive control C(+) was given 0.5% CMC Na before mosquito coil smoke exposure, and three groups that treated with 150 T(1), 300 T(2), and 600mg/kgBW T(3) of basil leaves extract before mosquito coil smoke exposure. Exposure to mosquito coil smoke was given for 8 hours a day for 52 days. All rats were terminated after 52 days of treatment; the histopathology of the lungs was observed under the microscope at 400× magnification within five visual different fields. The analysis was done by observing the severity. Statistical analysis in this study used Kruskal-Wallis and Mann-Whitney test.  Results: The result showed that the control group and treatment group had significantly different lung damage (p<0.05). Conclusion:  All doses of basil leaf extract reduce lung damage in infiltration of inflammation of  cells, thickening of alveolar wall, and enlarge alveolar in rats. The effective dose of basil leaf extract is 600 mg/kgBW in reducing the lung damage.